Suggestions for improving the effectiveness of environmental education in the maritime sector - Čulin, Jelena, inženjerka pomorskog prometa (Array, 2019)
Research shows that many barriers to pro-environmental behaviour in the maritime industry exist despite significant efforts of various stakeholders, and there is a need to put additional efforts to improve the sustainability of shipping. Education has an important role because a lack of environmental knowledge is almost always identified as a barrier to environmental concern and behaviour. However, eliminating knowledge gaps and raising concern does not necessarily translate to behaviour change, because behaviour depends on numerous factors, which moderate and mediate one another. Effectiveness of education activities may be improved if potential barriers are identified and targeted. This paper reviews determinants of pro-environmental behaviour and provides some suggestions for educators to plan and execute educational activities to increase the willingness of seafarers and shore-based personnel to adopt environmentally-friendly practices.